Relative preservation of facial expression recognition in posterior cortical atrophy - Pressman, Peter S. (Neurology, 2019)
OBJECTIVE: To compare recognition of facial expression (FE) vs recognition of facial identity (FI) in posterior cortical atrophy (PCA), with the hypothesis that FE recognition would be relatively preserved in PCA. METHODS: In this observational study, FI and expression recognition tasks were performed by 194 participants in 4 groups, including 39 with Alzheimer disease (AD) (non-PCA), 49 with behavioral variant frontotemporal dementia (bvFTD), 15 with PCA, and 91 healthy controls. Between-group differences in test scores were compared. RESULTS: Patients with PCA performed worse than healthy controls in FI and emotion recognition tasks (p < 0.001 for all). Patients with PCA also performed worse than AD and bvFTD groups in FI recognition, with no difference in FE recognition. CONCLUSIONS: Patients with PCA have relatively preserved FE recognition compared to FI recognition, as seen in affective blindsight.